Studies On The Flotation Of Cassiterite And Struve Rite - Hussin, Kamarudin (1993)
The flotation of cassiterite and struverite by tetra-sodium sulphosuccinamate as a collector was examined in the light of adsorption studies and zeta potential measurements. It was observed that the flotation and the adsorption of the collector on cassiterite are optimum around pH 3.0. In zeta potential meas uremen ts, it was observed that sulphosuccinamate substantially affects the zeta potentials of cassiterite, lowering its Le.p from pH 2.5 to pH 2.0 and indicating a specific adsorption and/or chemical interaction. For the struverite sample studied, the flotation and adsorption were optimum at the pH 3.0. In zeta potential studies, it was found that sulphosuccinamate substantially affects the zeta potentials of struverite, lowering its i.e.p from 2.5 to 2.0 and indicating a specific adsorption and/or' chemical interaction.